From Liquor to LPG: Spillover effects of alcohol prohibition on clean fuel adoption - Gaurav Dhamija; Sagnik Kumar Gupta; Manini Ojha (Global Labor Organization (GLO), 2026)
This paper examines whether Bihar's 2016 alcohol prohibition generated spillover effects on household adoption of Liquefied Petroleum Gas (LPG) as a primary cooking fuel. Although clean cooking lies outside the policy's intended scope, prohibition may affect fuel choice by altering household expenditure patterns and intra-household dynamics. Using repeated cross-sectional data from the Household Consumption Expenditure Surveys (HCES) of 2011-12 and 2023-24, we implement a propensity score matching difference-in-differences design, comparing Bihar with Jharkhand. We estimate that the prohibition increased primary LPG adoption by 12.8 percentage points. The effect is concentrated in rural areas and is robust to alternative estimators, sample restrictions, and falsification tests. We further discuss that this spillover operates through reduced alcohol spending that relaxes the budget constraint for recurring LPG use and improved women's intra-household agency following prohibition. The results highlight that policies aimed at curbing socially costly consumption can generate broader welfare gains in unexpected domains, including clean energy adoption.
Keywords: D12; I18; I31; J16; 330; Clean cooking; LPG adoption; Alcohol prohibition; Expenditure reallocation; India